The Impact of Antithrombotic Therapy in Patients with Decompensated Heart Failure and Iron (Balneo and PRM Research Journal, 2022)
The iron deficient anaemia is a common medical condition in patients with heart failure receiving antithrombotic therapy. Especially during the COVID19 pandemic period the rate of bleeding complications associated with the antithrombotic therapy tend to be higher, as the patient’s referral to medical services is lower and the interaction doctor-patient is limited. In our retrospective observational study we included 300 consecutive patients with decompensated heat failure associating iron deficient anaemia. For defining the medical conditions we used the ESC guidelines terminology and diagnostic criteria. We assessed the association between the iron deficient anaemia and different antithrombotic therapies, recommended in concordance to ESC Guidelines. We found that aspirin 75mg/day was statistical significant associated with iron deficient anaemia (p 0.012) and anaemia severity (p 0.002), this association  being assessed by Chi square and Pearson tests. Also, neither clopidogrel, ticagrelor, VKA or non-VKA were associated to the presence of anaemia. By assessing the mortality rate associated to anaemia severity, the severe anaemia was associated to higher mortality rate, meanwhile no antithrombotic therapy was associated with higher readmission or mortality rate (p